Completeness of reporting of quality improvement studies in neonatology is inadequate: a systematic literature survey - Lehana Thabane; Lawrence Mbuagbaw; Zheng Jing Hu; Salhab el Helou; Gerhard Fusch; Catherine Hu; Jie Yi Wang; Zoe el Helou; Muhammad Taaha Hassan (BMJ Open Quality)
Introduction Quality improvement (QI) is a growing field of inquiry in healthcare, but the reporting quality of QI studies in neonatology remains unclear. We conducted a systematic survey of the literature to assess the reporting quality of QI studies and factors associated with reporting quality.Methods We searched Medline for publications of QI studies from 2016 to 16 April 2020. Pairs of reviewers independently screened citations and assessed reporting quality using a 31-item modified Standards for Quality Improvement Reporting Excellence, 2nd edition (SQUIRE 2.0) checklist. We reported the number (percentage) of studies that reported each item and their corresponding 95% CIs. We used Poisson regression to explore factors associated with reporting quality, namely, journal endorsement of SQUIRE 2.0, declaration of funding sources, year of publication and number of authors. The results were reported as incidence rate ratio (IRR) and 95% CI.Results Of 1921 citations, 336 were eligible; among them, we randomly selected 100 articles to assess reporting quality. The mean (standard deviation) number of SQUIRE 2.0 items adhered to was 22.0 (4.5). Percentage of articles reporting each item varied from 26% to 100%. Journal endorsement of SQUIRE 2.0 (IRR=1.11, 95% CI 1.02 to 1.21, p=0.015), declaration of funding sources and increasing number of authors were significantly associated with better reporting.Conclusions Reporting quality of QI studies in neonatology is inadequate. Endorsing the SQUIRE 2.0 guideline is a step that journals can implement to enhance the completeness of reporting.